2019
DOI: 10.2478/amtsb-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Transteoretical Approaches on Domestic Violence

Abstract: Domestic violence is a widespread public health problem. Domestic violence does not just manifest itself physically, it can take different forms, from verbal aggression to insults of psychological, emotional, sexual, material deprivation or simply negligence. All these affect the victim in many ways. Thus, the professionals in medical, legal sciences, but also the state authorities with responsibilities in social protection and assistance must know the phenomenon very well and find the best ways to fight it. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…As such, it is important to adhere to the gendered inclusive approach in order to avoid missing other factors that play a role in IPV. The gender inclusive approach to IPV allows for the use of multifactorial explanations of the mechanics of IPV of which can include patriarchal values alongside other factors found to play a role in IPV (Popa-Nedelcu et al, 2019). It is dangerous and potentially unethical to limit research to focus on solely one aspect of IPV as suggested by gendered theory as this restricts the ability to gain the best understanding of IPV possible, and therefore restrict the production of the best methods to reduce the impact of IPV.…”
Section: Poster Conditionmentioning
confidence: 99%
“…As such, it is important to adhere to the gendered inclusive approach in order to avoid missing other factors that play a role in IPV. The gender inclusive approach to IPV allows for the use of multifactorial explanations of the mechanics of IPV of which can include patriarchal values alongside other factors found to play a role in IPV (Popa-Nedelcu et al, 2019). It is dangerous and potentially unethical to limit research to focus on solely one aspect of IPV as suggested by gendered theory as this restricts the ability to gain the best understanding of IPV possible, and therefore restrict the production of the best methods to reduce the impact of IPV.…”
Section: Poster Conditionmentioning
confidence: 99%